2021
DOI: 10.3390/antiox10081214
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Bioactive Profile, Antioxidant and DNA Damage Protection Potential of Rye (Secale cereale) Flour

Abstract: Six different solvents were used as extraction medium (water, methanol, ethanol, acidified methanol, benzene and acetone) to check their phenolics extraction efficacy from flour of two rye cultivars. Rye extracts with different solvents were further analyzed for the estimation of phytochemicals and antioxidant properties. Different tests (TPC, TAC, DPPH, FRAP, ABTS, RPA and CTC) were performed to check the antioxidant properties and tannin contents in extracts. A bioactive profile of a rye cultivar indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 59 publications
1
10
0
1
Order By: Relevance
“…Since chronic gingivitis is the result of failure in immune system against dysbiotic change, enhancing the host defense system, which is called host modulation therapy, can reduce gingival inflammation in the same dental plaque accumulated condition [10]. Various phenolic compounds from L. stenocephala and S. cereal supports the host defense system with its antioxidant ability and reduces periodontal tissue destruction with anti-inflammatory effect such as suppressing nuclear factor κβ, interleukin-6, -10 and -1β [13,27]. The previous review reported various medicinal plants as having antioxidant and phytochemicals which can modulate cellular signaling pathway; also, these medicinal plants can be potential candidates for gingivitis therapeutic [28].…”
Section: Discussionmentioning
confidence: 99%
“…Since chronic gingivitis is the result of failure in immune system against dysbiotic change, enhancing the host defense system, which is called host modulation therapy, can reduce gingival inflammation in the same dental plaque accumulated condition [10]. Various phenolic compounds from L. stenocephala and S. cereal supports the host defense system with its antioxidant ability and reduces periodontal tissue destruction with anti-inflammatory effect such as suppressing nuclear factor κβ, interleukin-6, -10 and -1β [13,27]. The previous review reported various medicinal plants as having antioxidant and phytochemicals which can modulate cellular signaling pathway; also, these medicinal plants can be potential candidates for gingivitis therapeutic [28].…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan has also been made a reference polymer in order to manufacture active packaging with the improvement or capability to prevent the growth of microorganisms and upgrade the safety of food [178]. It is feasible to create food packaging items that are safe against a broad range of modifying and pathogenic microbes by mixing chitosan with other natural antimicrobial agents [178,207,208]. Chitosan also can be used as a thin edible film/coating with food several methods such as by dipping, spraying, and pulverizing the film forming solution with an aerosol spray coating [214][215][216], as shown in Figure 17.…”
Section: Food Packagingmentioning
confidence: 99%
“…Chitosan has also been made a reference polymer in order to manufacture active packaging with the improvement or capability to prevent the growth of microorganisms and upgrade the safety of food [ 178 ]. It is feasible to create food packaging items that are safe against a broad range of modifying and pathogenic microbes by mixing chitosan with other natural antimicrobial agents [ 178 , 207 , 208 ].
Figure 17 ( A ) Development of chitosan/gelatin-based polymeric films with inclusion of citrus essential oils [ 209 ]; ( B ) preservation mechanism of chitosan-based coating to maintain quality of vegetables and fruits [ 210 ]; ( C ) multifunctional coating composed of Eryngium campestre essential oil encapsulated in nano-chitosan to prolong the shelf-life of fresh cherry [ 211 ]; ( D ) edible film’s antimicrobial activity against E. coli O157:H7 on cherry tomatoes [ 212 ].
…”
Section: Application Of Chitosan-based Green Compositesmentioning
confidence: 99%
“…Polyphenol extraction from rye flour that employed six different solvents (water, methanol, ethanol, acidified methanol, benzene and acetone) was assayed. The results indicated that the maximum antioxidant capacity was shown in water extracts, which is positive from an environmental and human consumption point of view [ 16 ]. Another friendly environmental process, known as the enzymatic process, was applied for vegetable juice inoculated with two lactic acid bacteria from kimchi.…”
Section: Extraction Methods Of Natural Antioxidantsmentioning
confidence: 99%